Primary Education Undergraduates’ Competency in the Use of Artificial Intelligence for Learning in Kwara State - Agarry, Rachael Ojima; Omolafe, Eyiyemi Veronica; Animashaun, Victoria O.; Babalola, Ebenezer Omolafe (ASEAN Journal of Educational Research and Technology, 2022)
The goal of this study is to bridge the gap created by classroom learning by incorporating the power of current technological innovation, especially the use of Artificial Intelligence (AI) among primary education undergraduates. This study presumed that to make a successful transition to knowledge-based education, the introduction of AI would be a necessary tool to shift Nigerian education from analog to digital. Hence, this study investigated the primary education student competency in the use of AI for learning. This study adopted descriptive research of the survey type. The findings of the study were that majority of the primary education undergraduates are not skilled and incompetent in the use of AI for learning. There was no significant difference between male and female primary education undergraduate’s competency in the use of AI for learning. There was no significant difference in primary education undergraduate’s competency in the use of AI for learning based on university proprietorship. Students' ability to explore digital resources such as AI depends on their access to digital technologies. AI technologies should be made available, open, and accessible to primary education undergraduates, to encourage them to utilize the technologies for learning to improve learners’ capability towards achieving better academic performance.